Liza Marić Križanić: Beauty and Sensibility (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
The history of Serbian art is often unjust towards artists, especially women who did not show ambition to emphasize their creation at all costs, or to make it more visible in the public eye. They most often lived in the shadows of their famous husbands, fathers or brothers. That is the case of Draginja-Draga Marić, better known as Liza Križanić, a beautiful, educated artist and the muse of many significant painters, sculptors and writers. According to Vera Jovanović, who wrote a comprehensive monograph about the author, despite her active presence in the artistic life of Belgrade, Liza Križanić appeared on the Serbian artistic scene more prominently just before World War II as an already accomplished artist. Even though she and her husband were friends with many other prominent artists of that age, Liza never took them as direct role models and tried to remain true to her artistic expression, always trying to find her own path. Aside from her own literary opus of around four hundred works, she was also the muse of many famous artists and her image can be found on some forty paintings. Some historians of Serbian art place Liza Križanić as one of the more significant representatives of poetic impressionism of the first half of the twentieth century.
Keywords: Liza Križanić; poetic impressionism; women artists; individual expression